Fracture Propagation Behavior of Jointed Rocks in Hydraulic Fracturing - Xiaoxi Men; Jiren Li; Zhihui Han (Advances in Materials Science and Engineering)
Jointed rocks are typical examples of heterogeneous materials with joints. The existence of joints influences the physical properties of rock mass and propagation of fractures, which can affect production operations in engineering. A series of simulations is performed to understand the failure patterns and fracture propagation behavior of jointed rocks in hydraulic fracturing. Three points, that is, dip-angle joint, joint strength, and complex joints, are considered in the simulations. Results demonstrate three basic kinds of hydraulic fractures on jointed rock, namely, along the joint, across the joint, and partly along the joint and partly across the joint. The maximum principal stress is the control factor of fracture propagation in global scale, and the joint plane is the control factor of fracture propagation in local scale. In the propagation path, when the dip angle is small or the joint is weak, the fracture propagates along the joint; otherwise, the fracture propagates across the joint. In the multijoint interconnection models, hydraulic fractures propagate along joints in the tensile stress regions near the propagating fracture tip without dip angle limitation. Subsequently, the fractures connect with one another to form a complex fracture network based on the joint morphology.